PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN DIREKSI TERHADAP PROFITABILITAS BUMN SEKTOR NON KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Romi Yunani; Istianingsih; David Pangaribuan (Economicus : Jurnal Ekonomi dan Manajemen, 2026)
This study aims to examine the effects of board characteristics—age, gender, educational level, educational relevance, board size, tenure, and the Board Index—on the profitability of non-financial state-owned enterprises (SOEs). It also investigates the moderating role of firm size in these relationships. The study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. Board characteristic data were collected from the annual reports of non-financial SOEs for the period 2019–2024. A total of 224 firm-year observations were obtained through purposive sampling. The analysis includes testing direct effects and moderating effects using the bootstrapping procedure. The findings indicate that all board characteristics, including the Board Index, do not significantly influence profitability. However, firm size significantly moderates the relationship between the Board Index and profitability (original sample = 0.137; t = 2.003; p = 0.045). The effectiveness of boards in enhancing financial performance is driven more by organizational dynamics and governance quality than by demographic attributes alone.